Algorithms in bioinformatics - Benson Gary ed.; Workshop on Algorithms in Bioinformatics, WABI 2003; Workshop on algorithms in bioinformatics, WABI 2003 Budapest, Hungary 15-20 Sep 2003 (New Delhi Springer(India), 2004)
This book constitutes the refereed proceedings of the Third International Workshop on Algorithms in Bioinformatics, WABI 2003, held in Budapest, Hungary, in September 2003. The 36 revised full papers presented were carefully reviewed and selected from 78 submissions. The papers are organized in topical sections on comparative genomics, database searching, gene finding and expression, genome mapping, pattern and motif discovery, phylogenetic analysis, polymorphism, protein structure, sequence alignment, and string algorithms.
Keywords: Applied statistics; Bioinformatics; Computer algorithms